Effect of clove cigarette exposure on white rat : special emphasis on the histopathology of respiratory tract (Faculty of Medicine Universitas Indonesia, 2007)
Cigarette smoke is proved to cause various disturbances on respiratory tract. Clove cigarette is far more dangerous than common (